2017
DOI: 10.35762/aer.2017.39.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CO2 Emissions from Vehicles in Thailand

Abstract: Emission of carbon dioxide (CO2), a greenhouse gas, from typical passenger vehicles in Thailand was investigated using a chassis dynamometer in the Automotive Emission Laboratory. The vehicle running method was controlled under the standard Bangkok driving cycle. CO2 emissions were measured at three different speeds for the following four vehicle types commonly used in Thailand: heavy duty diesel (HDD), light duty diesel (LDD), and light duty gasoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…It is clear that the impact of energy consumption on CO2 emissions is greater in the long-run followed by the short-run. The result is linked with the previous studies of Nilrit et al (2017), Ohlan (2015) and Hammami and Saidi (2015) where it confirmed that higher energy demand largely increases CO2 emissions in different economic settings. The impact of per capita GDP on CO2 emissions is negative, as if there is 1% increase in GDP, CO2 emissions decreases by -0.441% in the short-run and -0.634% in the long-run.…”
Section: Ardlsupporting
confidence: 84%
See 1 more Smart Citation
“…It is clear that the impact of energy consumption on CO2 emissions is greater in the long-run followed by the short-run. The result is linked with the previous studies of Nilrit et al (2017), Ohlan (2015) and Hammami and Saidi (2015) where it confirmed that higher energy demand largely increases CO2 emissions in different economic settings. The impact of per capita GDP on CO2 emissions is negative, as if there is 1% increase in GDP, CO2 emissions decreases by -0.441% in the short-run and -0.634% in the long-run.…”
Section: Ardlsupporting
confidence: 84%
“…A co-integration analysis is conducted, and results show a positive relationship between economic growth and emission in long run. Nilrit et al (2017) highlight the impact of urbanization and energy consumption on carbon dioxide emission in the economy of Thailand. Data is taken from 1971 to 2010.…”
Section: Introductionmentioning
confidence: 99%